Argentina : Technical Assistance Report-Report of the Technical Assistance Mission on External Sector Statistics (April 17-28, 2017). - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2019)
At the request of the National Statistics and Census Institute (INDEC), a technical assistance mission on external sector statistics (ESS) visited Buenos Aires during April 17-28, 2017. This was a follow up to the November 2016 mission that evaluated the ESS methodology, information sources, and dissemination policy and made recommendations to improve quality, adapt the production of ESS to the methodology provided by the Balance of Payments and International Investment Position Manual, Sixth Edition (BPM6), and support the quarterly compilation and dissemination of the International Investment Position (IIP) in accordance with the Special Data Dissemination Standards (SDDS). The mission reviewed the implementation status of the tasks identified in the action plan prepared by the November 2016 mission; assisted compilers in preparing quarterly ESS in accordance with BPM6 guidelines for the next quarterly publication; and provided practical advice on the methodology to be used.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet